Nurse phone interview prior to colonoscopy - What is the benefit on bowel preparation results and safety? - Taveira, Filipe (2018)
Aims: To understand the added value of a nurse phone interview on the colonoscopy preparation process regarding bowel preparation results and medication safety. Methods: Prospective collected data of outpatients referred from other departments to perform a total colonoscopy at our department, who received a prior educational call from the nursing staff, from January to October 2017. Collected demographic data, time and contact duration, chronic medication (insulin, oral antidiabetic, anticoagulant, antiplatelet, iron), laxative and diet prescribed. If advisable, changes were suggested according to predefined medical rules. After the colonoscopy, the patient was asked about compliance with indications. Bowel preparation was graded by the Boston Bowel Preparation Scale (BPSS). Results: Collected 233 consecutive complete questionnaires, male 52.4%, mean age 68 (± 11 years). The median time span since the call was 6 days prior to the exam (IQR 2 - 10), with a median duration of 10 minutes (IQR 3 - 17). The patient was directly contacted in 70% (n = 163). Changes in chronic medication were suggested in 25% (n = 58). Six patients (2.6%) did not know the laxative brand to use and 13.3% were unaware of the correct time to perform the laxative. The timetable for laxative ingestion was altered in 170 patients (73%). Absence of any dietetic recommendation detected in 15.9% (n = 37), with suggestions to dietetic adjustments in 44.6% (n = 104). Indications were not followed by 40 patients (17,2%). A BPSS ≥6 was achieved in 89.6% of patients following indications versus 52.5% when not. On multivariate analysis, only the failure to follow nurse recommendations was significant to a poor BPSS outcome (OR 7, 95% CI, 3.28 - 15.08). Conclusions: A personalized nurse contact prior to colonoscopy can solve most problems related to its preparation, translating to a safer procedure and adequately prepared bowel. The inability to follow instructions is a problem in a considerable group of patients.